297 Bevacizumab in relapsed ovarian cancer: an indian tertiary care canter experience. (18th September 2019) - Das, CK; Rai, B; Rajwanshi, A; Dey, P; Srinivasan, R; Kalra, J; Bagga, R; Prasad, G; Jain, V; Suri, V; Saha, SC; Ghoshal, S
Abstract : Objectives: Bevacizumab, an anti-vascular endothelial growth factor antibody with chemotherapy improved the progression-free survival (PFS) in relapsed ovarian cancer. There is a paucity of data regarding the use of bevacizumab from the Indian subcontinent. Methods: We retrospectively reviewed the clinical data of patients with epithelial ovarian cancer (EOC) from the hospital database treated during 2016–2019. The progression-free survival (PFS), overall response rate (ORR) and toxicity profile analysed using IBM SPSS software version 25.0 (IBM Corp., Armonk, NY). Results: Sixty-two women with relapsed ovarian cancer were treated with bevacizumab (15mg/kg) and chemotherapy. The median age was 60 years (IQR 36–64). Platinum sensitive (PS) relapse constitutes 38/61(62.3%) and platinum resistant (PR) disease in 23/61(37.7%). The ORR in PS and PR groups are 59% and 26% respectively. Compared with the PR group, the PS group achieved a significantly longer one-year PFS (64% vs 9.3%, P<0.004). The toxicity profile is not statistically significant between the two groups. Conclusions: The present study is the first Indian data on the outcome of relapsed ovarian cancer treated with bevacizumab-based therapy. Progression-free survival significantly higher in platinum-sensitive ca ovary patients as compared to platinum-resistant patients with an acceptable toxicity profile.